Social Media's Entertainment, Customization, and Trendiness Shape Brand Image and Purchase Intentions for Indonesian Women - Mohamat Basori (Management Study Program, Universitas Kristen Indonesia Paulus, 2026)
Social media's rapid growth has reshaped brand-consumer ties, especially for Indonesian women in e-commerce. This study probes how entertainment, personalization, and trendiness in social media marketing affect purchase intent, mediated by brand awareness and image, using Theory of Planned Behavior. Researchers surveyed 280 Indonesian women active on social media with online shopping experience. Quantitative data underwent Partial Least Squares Structural Equation Modeling analysis via SmartPLS 4.0. Personalization and trendiness significantly raised brand awareness, enhancing image and purchase intent. Awareness fully mediated their path to buying. Entertainment directly boosted intent but lacked impact on awareness or image. Brands targeting Indonesian women must emphasize custom, trendy content to build recognition and favor, driving sales. This integrates social media tactics into TPB for Asian contexts, guiding gender-focused digital strategies in Indonesia's online market.